THE ROLE OF DIVERSIFICATION OF BANKING SERVICES IN THE PROFITABILITY OF COMMERCIAL BANKS: AN ANALYTICAL STUDY IN THE IRAQI CREDIT BANK AND THE INTERNATIONAL DEVELOPMENT BANK (American Journal of Business Management, Economics and Banking, 2023)
This study was prepared to demonstrate the role of diversification of banking services in the profitability of private Iraqi commercial banks. international development), and the research tended to follow the inductive approach, the descriptive approach, and the analytical approach by studying the theoretical framework for diversifying banking services, indicators of profitability in commercial banks, the most important ratios measured, and analyzing the effects left by the diversification of banking services on the profitability of Iraqi private commercial banks, the research sample, in order to strive to achieve the goals set by him and trying to reach them by conducting this type of research.The problem of the study was embodied in the role of diversifying banking services in the profitability of Iraqi private commercial banks.The research also reached a set of conclusions, the most important of which are: The higher the level of diversification of banks in the services they provide to their customers, the higher the net profit and the rest of the profitability indicators, and this was evident in the study sample banks. Also, the high levels of diversification in banking services require a large financial capacity, due to the high cost of producing new services, in addition to its ability to maintain its current business. The research also presented a set of recommendations, the most important of which are: the need for banks to raise the level of their diversification in banking services, because of this important role in the profitability of commercial banks, as diversification contributed to the entry of banks into some areas of new business and thus increase their ability to compete and improve profitability.